The Representation of Success in the Song Champion (2017) by Fall Out Boy featuring RM - Julianti, Raninda (English Department, Faculty of Humanities, Andalas University, 2022)
This research was conducted to analyze the representation of success defined in the song Champion (2017) by Fall Out Boy featuring RM of BTS, which is also using the figure of speech found in the song. The method used in this research is descriptive qualitative. The theory that helps this research is the representation theory introduced by Stuart Hall. This study finds a unique representation of the definition of success in the song Champion (2017) by Fall Out Boy featuring RM of BTS. It was found that the song defines success as success in managing mental health in young people. The song describes the mental health state of young people who continue to have anxiety about the future. The pressure is described as being obtained from the surrounding environment. However, the song describes self-compassion to not be too hard on their selves because the most critical success is mental health. The song represents success in caring towards mental health as more important than the success that is pressured by the surroundings.